New guidelines adopted in Madagascar and Benin in 2018 to implement laws passed in 2017 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
CGIAR Research Innovation: Decision-making tools for developing national laws and guidelines to implement the Plant Treaty; tools and methods for discovering potentially adapted materials for use in climate stressed local ag production systems Users of Innovation: National partners, including competent national authorities responsible for implementing the Plant Treaty and the Nagoya Protocol used the decision making tool when developing the national laws and policies adopted. Nature of outcome: Guidelines for implementation of national laws adopted and published by lead agencies.